The Singleton Fallacy: Why Current Critiques of Language Models Miss the Point - Sahlgren, Magnus; Carlsson, Fredrik (Frontiers in Artificial Intelligence, 2021)
This paper discusses the current critique against neural network-based Natural Language Understanding solutions known as language models. We argue that much of the current debate revolves around an argumentation error that we refer to as the singleton fallacy: the assumption that a concept (in this case, language, meaning, and understanding) refers to a single and uniform phenomenon, which in the current debate is assumed to be unobtainable by (current) language models. By contrast, we argue that positing some form of (mental) "unobtanium" as definiens for understanding inevitably leads to a dualistic position, and that such a position is precisely the original motivation for developing distributional methods in computational linguistics. As such, we argue that language models present a theoretically coherent approach that is our current best bet for computers to achieve language understanding. This understanding must however be understood as a computational means to an end.